ChemInform Abstract: Palladium‐Catalyzed Intramolecular Cyclization of 2‐Iodobenzamides: An Efficient Synthesis of 3‐Acyl Isoindolin‐1‐ones and 3‐Hydroxy‐3‐acylisoindolin‐1‐ones. Issue 5 (4th February 2014) - Chen, Wanli; Jin, Lina; Zhu, Yinghong; Cao, Xiaoji; Zheng, Lebin; Mo, Weimin
Abstract An efficient Pd‐catalyzed cyclization of ortho‐iodobenzamides (I) is developed to give 3‐acylated isoindolin‐2‐ones (II) in moderate to good yields.